2015
DOI: 10.1155/2015/630585
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofJatropha curcasL. Protein Cast Films with respect to Packaging Relevant Properties

Abstract: There is increasing research ongoing towards the substitution of petrochemical based plastics by more sustainable raw materials, especially in the field of bioplastics. Proteins of different types such as whey, casein, gelatine, or zein show potential beyond the food and feed industry as, for instance, the application in packaging. Protein based coatings provide different packaging relevant properties such as barrier against permanent gases, certain water vapour barrier, and mechanical resistance. The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
1
7
1
Order By: Relevance
“…However, the light transmission in visible ranges of WPC films was lower than 80% for the entire visible range. This result is consistent with Gofferje et al ., who reported that the protein films prepared from Jatropha curcas L. appeared brownish and not transparent to the human eye. However, this result is in contrast with Schmid et al ., who reported that whey protein isolate films showed to be highly transparent, and the films sample reached a transmittance over 80%.…”
Section: Resultssupporting
confidence: 93%
“…However, the light transmission in visible ranges of WPC films was lower than 80% for the entire visible range. This result is consistent with Gofferje et al ., who reported that the protein films prepared from Jatropha curcas L. appeared brownish and not transparent to the human eye. However, this result is in contrast with Schmid et al ., who reported that whey protein isolate films showed to be highly transparent, and the films sample reached a transmittance over 80%.…”
Section: Resultssupporting
confidence: 93%
“…Gofferje et al . found a TS of 2 Mpa for jatropha protein (61.2%) films containing 30% glycerol . In this study, the JC film had a TS of 2.32 Mpa, which was 16% greater than that reported by the above mentioned work.…”
Section: Resultscontrasting
confidence: 61%
“…Gofferje et al . reported that the lipid content affected the smooth appearance of jatropha films plasticized with glycerol . Ogale et al .…”
Section: Resultsmentioning
confidence: 99%
“…Bioplastics or edible films are commonly produced using proteins (Blanco-Pascual et al 2014;Chang and Nickerson 2014;Hammann and Schmid 2014;Gofferje et al 2014), lipids (Chiumarelli and Hubinger 2014), polysaccharides (Antoniou et al 2014;Jost et al 2014;Pan et al 2014a), or mixed composite blends (Kowalczyk and Baraniak 2014;Marquez et al 2014;Pan et al 2014b;Winkler et al 2015). In general, polysaccharides and proteins provide mechanical stability and good gas barrier properties, while fats are used to minimize water transmission (Pavlath and Orts 2009).…”
Section: Introductionmentioning
confidence: 99%